Studies on the genus Ripersiella Tinsley (Hemiptera: Coccomorpha: Rhizoecidae) in the Neotropical region, with description of a new species - Szita, Éva; Benedicty, Zsuzsanna Konczné; Kondo, Takumasa; Ramos-Portilla, Andrea Amalia; Kaydan, Mehmet Bora (Zootaxa, 2020)
The Neotropical scale insect genus Ripersiella Tinsley (Hemiptera: Coccomorpha: Rhizoecidae) was investigated, based on soil samples deposited at the Hungarian Natural History Museum. Description and illustration of a new species, Ripersiella incarum Kaydan & Szita sp. n., and an identification key and new additional locality records for the currently known Ripersiella species in the Neotropical region, are provided and discussed.